Where the Heart is Mitchell - Mitchell, Ann, 1935- (Canada : Boston Mills Press, 1996)
Where the Heart Is features a selection of paintings drawn from the past twenty years of Ann Mitchell's career. Rooted in the Naive tradition, each painting captures real people in real situations and evokes a love of place that is often overlooked in modern life. Homes, churches, farms, schools, a train station -- Mitchell's paintings and accompanying writings tell the stories that bind people to their place.
Keywords: Mitchell, Ann, -- 1935-.